Security from the peace of Westphalia to sustainable development - CRUZ, EDWIN (2022)
The objective of this article is to show the evolution of security concepts; at the end of the 30-year war (1618-1648), signing the peace of Westphalia, between the European powers; the conception of the Nation-State, concepts such as sovereignty, territorial integrity. The nascent American nation "United States of America", executed the doctrine of "manifest destiny". US President James Monroe proclaimed before the United States Congress his famous phrase "America for the Americans", in an open speech threatening any colonizing power, which would incite to regain control of the nascent American republics in the Western Hemisphere, initiating the incipient concept of "Hemispheric Security". With the rising European threat of Nazism, institutions were created on the continent to face these threats, such as the Inter-American Defense Board (IADB-1942), we appreciate the concept of “Collective Security”. Before the end of the Second World War (1939-1945), the United Nations Organization (UN) was created, the term "International Security" was born. With the end of the Second World War and the beginning of the Cold War, the world becomes bipolar with the influence of the USA and the USSR; In the Western Hemisphere, in 1947 the Inter-American Treaty of Reciprocal Assistance (TIAR) was created, emphasizing the concept of “Collective Security”. With the evolution of economic interests and free trade agreements to avoid conflict between members of regional (OAS) and international (UN) organizations, the concept of "Cooperative Security" evolves. In 1994, the report of the United Nations Development Program (UNDP), highlights the term from the Security of the States to the Security of the People, “Human Security”. In the Declaration of Bridgetown (2002): The multidimensional approach to hemispheric security, "Multidimensional Security", is agreed. And it is emphasized in Mexico City 2003 "In the Declaration of the Americas", and that the traditional concept and approach should be expanded to include new and non-traditional threats, which include political, economic, social, health and environmental aspects. The new US National Security Strategy (2009), in which it more clearly defines the main elements of the new security model being advocated. Likewise, China agrees with the US in the new approach to "Sustainable Security."